Finite-time synchronization of multi-scroll chaotic systems with sigmoid non-linearity and uncertain terms - Mishra A.K.; Das S.; Yadav V.K. (My University, 2025)
In this article, the finite-time synchronization of multi-scroll chaotic systems with sigmoid non-linearity in the presence of uncertain stochastic parameters has been studied. The finite-time synchronization is a popular topic from a practical point of view in engineering, which has many applications in the areas like chaos-based communication, image and voice encryptions. The present chaotic system scrolls (up to five) are incorporated with the help of hyperbolic tangent functions (sigmoid non-linearity), but in real applications, there is no limit of multi-scroll in a chaotic system. Finite-time synchronization is achieved with the help of Lyapunov stability using some lemmas and definitions. The Lyapunov exponents are also calculated for multi-scroll chaotic systems with uncertainties and it confirms that the multi-scroll system is chaotic with uncertainties. A drive has been taken to achieve finite-time synchronization of multi-scroll chaotic systems with uncertain parameters, where the multi-scrolls are generated by nonlinear functions. © 2020